Landforms Spatial Interference with Seismic Waves in the Area of Influence of the Cocos Plate, Mexico - Martínez-García, Fidel (Anuário do Instituto de Geociências, 2022)
Within the framework of the “site effect” study and the spatial impact of local geographic features on seismic waves, the maximum accelerations of 45 interplate and intraslab seismic events with magnitudes (Mw) in the range of 5.6 to 8.2 that occurred from 1985 to 2018 were spatially analyzed and processed. Averages and maximum acceleration values of 172 accelerographs distributed among the territories boundaries located in the most seismic region of Mexico, are replaced the data of the scale of seismic moment magnitude (Mw) in each of the epicenters of the 45 events studied. The differential seismic impact of the topography that four Significant Epicentral Zones (SEZ) identified exert in two important cities, two tourist poles and two commercial seaports is identified. Correspondingly, the predominant orientation, direction, spatial tendency at the lithosphere level, which follow seismic waves as a result of interaction with topography within each SEZ were identified.